Clinical presentation, diagnostic features on cardiac magnetic resonance imaging and outcome of patients with cardiac amyloidosis presenting to a tertiary care setting - Fateh Ali Tipoo Sultan; Muhammad Taha Khan (Journal of the Pakistan Medical Association, 2022)
Cardiac amyloidosis is a rare disease which is under diagnosed in this region. This study was aimed to assess the clinical presentation, cardiac magnetic resonance imaging findings and prognosis of patients with cardiac amyloidosis in Pakistani population presenting to a tertiary care setting. A total of eight patients were included with the confirmed diagnosis of cardiac amyloidosis on CMR, after reviewing the CMR data of Aga Khan University Hospital from January 2011 to August 2019. Mean age was 51 + 11.5 years with the majority (75%) being male. All patients presented with heart failure. Sub optimal myocardial nulling on late gadolinium images was the most common finding on CMR. Late gadolinium enhancement was diffuse transmural in 5 patents (62.5%) and diffuse sub-endocardial in 3 patients (37.5%). On a mean follow up of 14 + 10 months, 3 patients (37.5%) died while 7 patients (87.5%) had hospital admissions due heart failure.